Asymptomatic Participants With a Femoroacetabular Deformity Demonstrate Stronger Hip Extensors and Greater Pelvis Mobility During the Deep Squat Task. Issue 7 (17th July 2018) - Catelli, Danilo S.; Kowalski, Erik; Beaulé, Paul E.; Smit, Kevin; Lamontagne, Mario
Background: Cam-type femoroacetabular impingement (FAI) is a femoral head-neck deformity that causes abnormal contact between the femoral head and acetabular rim, leading to pain. However, some individuals with the deformity do not experience pain and are referred to as having a femoroacetabular deformity (FAD). To date, only a few studies have examined muscle activity in patients with FAI, which were limited to gait, isometric and isokinetic hip flexion, and extension tasks. Purpose: To compare (1) hip muscle strength during isometric contraction and (2) lower limb kinematics and muscle activity of patients with FAI and FAD participants with body mass index–matched healthy controls during a deep squat task. Study Design: Controlled laboratory study. Methods: Three groups of participants were recruited: 16 patients with FAI (14 male, 2 female; mean age, 38.5 ± 8.0 years), 18 participants with FAD (15 male, 3 female; mean age, 32.5 ± 7.1 years), and 18 control participants (16 male, 2 female; mean age, 32.8 ± 7.0 years). Participants were outfitted with electromyography electrodes on 6 muscles and reflective markers for motion capture. The participants completed maximal strength tests and performed 5 deep squat trials. Muscle activity and biomechanical variables were extrapolated and compared between the 3 groups using 1-way analysis of variance. Results: The FAD group was significantly stronger than the FAI and control groups during hip extension, and the FAD group had greater sagittal pelvic range of motion and could squat to a greater depth than the FAI group. The FAI group activated their hip extensors to a greater extent and for a longer period of time compared with the FAD group to achieve the squat task. Conclusion: The stronger hip extensors of the FAD group are associated with greater pelvic range of motion, allowing for greater posterior pelvic tilt, possibly reducing the risk of impingement while performing the squat, and resulting in a greater squat depth compared with those with symptomatic FAI. Clinical Relevance: The increased strength of the hip extensors in the FAD group allowed these participants to achieve greater pelvic mobility and a greater squat depth by preventing the painful impingement position. Improving hip extensor strength and pelvic mobility may affect symptoms for patients with FAI.